PERSONAL DATA PROTECTION LAW IN INDONESIA: CHALLENGES AND OPPORTUNITIES - Syailendra, Moody Rizqy; Lie, Gunardi; Sudiro, Ahmad (Indonesia Law Review, 2024)
This research identifies challenges, obstacles and opportunities related to the issuance of Law No. 27 of 2022. Protection of personal data is crucial, especially in the use of information and communication technology in the current modern era. The contents of this article were analyzed using qualitative methods and secondary data in analyzing it. The research results show that: although the PDP Law was only implemented in 2022, regulations regarding PDP can actually be found in various pre-existing regulations, then there are principles and provisions that can be included in the PDP Law to better accommodate the need for protecting people's personal data, Furthermore, there are various challenges, obstacles and protections in implementing the PDP Law. The conclusion is that the passing of Law Number 27 of 2022 concerning Personal Data Protection in Indonesia marks a significant step in strengthening personal data protection for Indonesian citizens. However, implementing this law presents various challenges that the government must overcome.